2014
DOI: 10.1371/journal.pone.0092894
|View full text |Cite|
|
Sign up to set email alerts
|

Motion-Induced Blindness and Troxler Fading: Common and Different Mechanisms

Abstract: Extended stabilization of gaze leads to disappearance of dim visual targets presented peripherally. This phenomenon, known as Troxler fading, is thought to result from neuronal adaptation. Intense targets also disappear intermittently when surrounded by a moving pattern (the “mask”), a phenomenon known as motion-induced blindness (MIB). The similar phenomenology and dynamics of these disappearances may suggest that also MIB is, likewise, solely due to adaptation, which may be amplified by the presence of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 32 publications
4
54
1
Order By: Relevance
“…It seems likely that these functional differences are due to the inherent asymmetry of MIB and would not occur in symmetric bistable phenomena, such as binocular rivalry (Brascamp et al 2006) or 3D structure from motion (Klink et al 2008). Despite the differences in symmetry, recent psychophysical work (Bonneh et al 2014) establishes analogous dynamical properties for MIB as for the above two phenomena. We thus hypothesize that analogous beta suppression effects as observed during MIB target disappearance will occur during all switches in these illusions.…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely that these functional differences are due to the inherent asymmetry of MIB and would not occur in symmetric bistable phenomena, such as binocular rivalry (Brascamp et al 2006) or 3D structure from motion (Klink et al 2008). Despite the differences in symmetry, recent psychophysical work (Bonneh et al 2014) establishes analogous dynamical properties for MIB as for the above two phenomena. We thus hypothesize that analogous beta suppression effects as observed during MIB target disappearance will occur during all switches in these illusions.…”
Section: Discussionmentioning
confidence: 99%
“…As for Troxler (1804) fading, the mechanisms underlying MIB was suggested to involve low-level processes such as contrast adaptation (Caetta, Gorea, & Bonneh, 2007;Gorea & Caetta, 2009), and filling-in (Hsu, Yeh, & Kramer, 2006), as well as depth ordering and surface completion (Graf, Adams, & Lages, 2002). However, recent findings show additional components in MIB related to the neural competition between the static target and the moving background (Bonneh et al, 2001;Bonneh et al, 2014;Donner, Sagi, Bonneh, & Heeger, 2008).…”
Section: Introductionmentioning
confidence: 93%
“…MIB disappearances last for up to several seconds, even with high contrast, relatively large stimuli, and when located near fixation: eccentricity of 18 (Bonneh et al, 2001;Bonneh, Donner, Cooperman, Heeger, & Sagi, 2014). As for Troxler (1804) fading, the mechanisms underlying MIB was suggested to involve low-level processes such as contrast adaptation (Caetta, Gorea, & Bonneh, 2007;Gorea & Caetta, 2009), and filling-in (Hsu, Yeh, & Kramer, 2006), as well as depth ordering and surface completion (Graf, Adams, & Lages, 2002).…”
Section: Introductionmentioning
confidence: 93%
“…The current study is the first to empirically demonstrate that MIB, TE, and PFI are all driven by this general timing mechanism. Moreover, whereas previous studies exploring commonalities between MIB, TE, and PFI have done so by making the tasks more similar to one another to control for potential contaminating sensory factors (e.g., Bonneh et al, 2014;Gorea & Caetta, 2009;Hsu et al, 2004Hsu et al, , 2006, the current study has taken an individual differences approach that does not substantially modify the stimuli. This leaves intact the basic constructs that are typically used to induce these types of illusory disappearances, making the current comparisons perhaps more directed as they use each phenomena's typical methods.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, it has been suggested that MIB and TE are both driven, at least in part, by an adaptation mechanism (Bonneh, Donner, Cooperman, Heeger, & Sagi, 2014;Gorea & Caetta, 2009). Particularly, it was shown that all MIB displays with rotating or stationary masks, as well as no masks display, caused a drop in sensitivity for the target, suggesting that adaptation contributed to the illusory disappearances in each condition (Gorea & Caetta, 2009).…”
Section: Comparing and Contrasting The Properties Of Illusory Disappementioning
confidence: 99%